A multi-country test of brief reappraisal interventions on emotions during the COVID-19 pandemic - Goldenberg, Amit; Eudave, Luis; Jackson, Emily A.; Garcia, Elkin Oswaldo Luis; Desai, Kermeka; Nadif, Khaoula; Bravo, Olalla Niño; van Steenkiste, I. M. M.; Adamkovič, Matúš; Adetula, Gabriel Agboola; Arinze, Nwadiogo Chisom; Vasilev, Martin R.; et al. (Nature human behaviour, 2021)
The COVID-19 pandemic has increased negative emotions and decreased positive emotions globally. Left unchecked, these emotional changes might have a wide array of adverse impacts. To reduce negative emotions and increase positive emotions, we tested the effectiveness of reappraisal, an emotion-regulation strategy that modifies how one thinks about a situation. Participants from 87 countries and regions ( n = 21,644) were randomly assigned to one of two brief reappraisal interventions (reconstrual or repurposing) or one of two control conditions (active or passive). Results revealed that both reappraisal interventions (vesus both control conditions) consistently reduced negative emotions and increased positive emotions across different measures. Reconstrual and repurposing interventions had similar effects. Importantly, planned exploratory analyses indicated that reappraisal interventions did not reduce intentions to practice preventive health behaviours. The findings demonstrate the viability of creating scalable, low-cost interventions for use around the world. Protocol registration The stage 1 protocol for this Registered Report was accepted in principle on 12 May 2020. The protocol, as accepted by the journal, can be found at https://doi.org/10.6084/m9.figshare.c.4878591.v1 This Registered Report presents evidence from 87 countries and regions showing that brief emotion-regulation interventions consistently reduced negative emotions and increased positive emotions during the COVID-19 pandemic.